Public Policy for Sustainability and Retail Resilience in Lisbon City Center - Barata-Salgueiro, Teresa (2020)
International organizations, public authorities and researchers have increasingly been concerned with urban resilience and sustainability. We focus on the triangle retail, urban resilience and city sustainability, aiming to uncover how cities have coped with retail challenges to increase their resilience towards a sustainable path, highlighting the role played by public policy. The case study asks, is Central Lisbon strongly affected by processes of regeneration, touristification and gentrification, simultaneously with changes in retail. The analysis of planning and other policy documents complemented by fieldwork evidence shows a close link between public initiatives and private entrepreneurship and their impacts in the vitality of the core. The text shows that the policy outlined by local authorities to overcome the decline of the city center and to meet the aims of sustainability implies urban resilience. The transformation of retail is aligned with that vision and is supported its achievement, while the commercial fabric suffered an evolution from shopping to consumption spaces, polarized by culture and entertainment, targeting new consumers and lifestyles. However, new social and economic challenges arise due to escalating housing prices, change in retail supply, the excessive dependence of tourism and the danger of losing part of the city’s identity.